2013
DOI: 10.1002/clen.201200266
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Parameters of Plant Communities Partially Reflect the Soil Quality Improvement in Eco‐Reclamation Area of an Opencast Coal Mine

Abstract: The influence of soil physicochemical properties and the relationship between the plant community and edaphic factors have been studied through monitoring the community dynamic parameters and analyzing the soil properties from four plant plots at the Pingshuo opencast coal mine eco-reclamation area. The results are obtained as follows:(1) the law of the quantity variation of total N and available K is affected by the different kinds of plant configuration mode. It is Robinia pseudoacacia þ Pinus tabuliformis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In accordance with previous studies [28], most of the soil nutrients measured in this study increased with the increase in restoration age (Figures 2-4), suggesting that a revegetative approach is effective to enhance topsoil recovery in refuse dumps. In general, plants can affect the soil nutrients [57], which may be attributed to the conversion from leaf litter fall to humus in the topsoil [30]. Thus, soil nutrients were relatively lower in the newly RA, as the seedlings and soil were in the initial stage of mutual feedback.…”
Section: Effects Of Mining and Restoration On Soil Properties And Plamentioning
confidence: 99%
“…In accordance with previous studies [28], most of the soil nutrients measured in this study increased with the increase in restoration age (Figures 2-4), suggesting that a revegetative approach is effective to enhance topsoil recovery in refuse dumps. In general, plants can affect the soil nutrients [57], which may be attributed to the conversion from leaf litter fall to humus in the topsoil [30]. Thus, soil nutrients were relatively lower in the newly RA, as the seedlings and soil were in the initial stage of mutual feedback.…”
Section: Effects Of Mining and Restoration On Soil Properties And Plamentioning
confidence: 99%
“…The result suggested that the succession of vegetation from herbaceous to shrub or liana may be sponsored after then 17 . Other researches also demonstrated that trends of species richness and diversity increased with increase in the age and common occurrence of certain shrubs and other species emerged after then [18][19][20] . As a result, shrub and liana plants grown in this pile not only suggested the future direction of succession, but also showed the good condition altered by the pioneering plants for the following colonized vegetation.…”
Section: Resultsmentioning
confidence: 99%